A high performance pick and a method for preparing the pick by laser cladding
By using body and high-energy laser cladding technology composed of specific elements on the teeth, combined with a variety of post-treatment processes, the wear resistance and service life of the teeth in high-strength environments is solved, and high hardness and low defects are achieved coating properties.
Patent Information
- Application Number
- CN202411426537.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing cutting teeth have short service life and are prone to wear in high-strength working environments. The traditional coating technology is costly and it is easy to produce defects such as internal stress, cracks and pores during the cladding process, which affects performance.
The toothed body consisting of elements such as C, Si, Mn, Cr, Mo, Re, Nb, S, P, etc. is used, and a thickness-controllable cladding layer is formed through sandblasting preheating and high-energy laser cladding technology, combined with nitric acid Catalytic degreasing, thermal degreasing, sintering and salt bath treatment to form high hardness and wear resistance teeth cutouts.
It significantly improves the hardness, wear resistance and fatigue resistance of the cut teeth, extends the service life, reduces the thermal stress of the cladding layer, avoids cracks and pore defects, and improves the mechanical properties of the coating.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal laser cladding, and more specifically, to a high-performance pick and a method for preparing the pick by laser cladding. Background Art
[0002] With the rapid development of modern industrial production, picks, as key components of mining equipment, play an extremely important role in mining, construction and other fields. Their performance directly affects mining efficiency and cost. However, existing picks have problems such as short service life, easy wear and damage under high-intensity working environments. In order to improve the wear resistance and service life of picks, coating technologies such as PVD (physical vapor deposition) and CVD (chemical vapor deposition) are often used. However, the coating thickness prepared by traditional surface coating technologies (such as PVD) is usually thin, which limits the wear resistance of the coating. PVD and other coating technologies usually need to be carried out in a vacuum environment, which has extremely high requirements on the environment and increases the processing cost. Laser cladding technology can prepare thicker cladding layers to improve the wear resistance and hardness of picks. However, some problems will occur during the laser cladding process, such as defects such as internal stress, cracks and pores, which affect the performance of the picks. Summary of the invention
[0003] In order to solve the technical problems mentioned in the background technology, the present application provides a high-performance pick and a method for preparing the pick by laser cladding.
[0004] In the first aspect, the present application provides a high-performance pick, which adopts the following technical solution:
[0005] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15-0.23%, Si: 2.10-2.60%, Mn: 2.40-2.60%, Cr: 0.80-1.20%, Mo: 0.35-0.50%, Re: 0.01-0.05%, Nb: 0.01-0.05%, S<0.02%, P<0.01%, the balance being Fe and unavoidable impurities, and the cladding layer is composed of 12-14 parts of iron-based alloy powder, 8-10 parts of nickel-based alloy powder, 6-8 parts of cobalt-based alloy powder, 1-2 parts of tungsten carbide, 1-2 parts of boron carbide and 1-2 parts of aluminum oxide.
[0006] Preferably, the method for preparing the pick body specifically comprises the following steps:
[0007] S1. Feed preparation:
[0008] The raw materials of the pick body are mixed to prepare alloy powder according to weight percentage, the alloy powder and the binder are added into a kneader, kneaded at a temperature of 130-160° C. for 90-120 minutes, and extruded and granulated to obtain feed material for standby use;
[0009] S2, molding degreasing:
[0010] The feed material is molded into a pick body, and then subjected to nitric acid catalytic degreasing and thermal degreasing processes to obtain a degreased blank;
[0011] S3, sintering treatment:
[0012] The degreased blank in step S2 is placed in a vacuum batch furnace, and after pre-sintering, the temperature is further increased to 1220-1280°C at a heating rate of 2.2-3°C / min, and the temperature is kept for 120-150min, and then sintered. After sintering, a dense blank is obtained by cooling.
[0013] S4, post-processing:
[0014] The dense blank in step S3 is heated to 1030-1060°C and kept warm for 1-2h. The dense blank is immersed in a salt bath at 320-340°C, kept warm for 1-2min, and then air-cooled to room temperature. The product after the salt bath treatment is heated to 550-600°C at a heating rate of 1-2°C / min, kept warm for 4-8h for primary aging, and then cooled to 450-550°C at a cooling rate of 4-8°C / min, and kept warm for 2-4h for secondary aging. After the insulation is completed, it is cooled to room temperature with the furnace to obtain the required high-performance pick body.
[0015] Preferably, the alloy powder D in step S1 50 The particle size is 7.5-8.5μm.
[0016] Preferably, the adhesive in step S1 is composed of a mixture of 8-10 parts of polyethylene, 3-4 parts of polymethyl methacrylate, 1-2 parts of polypropylene, 1-2 parts of polytetrafluoroethylene and 1-2 parts of stearic acid, wherein the polyethylene is a mixture of 65-70% of high-density polyethylene and 30-35% of low-density polyethylene.
[0017] Preferably, the added amount of the binder is 6-10% of the total mass of the alloy powder.
[0018] Preferably, the compression molding conditions in S2 are a compression pressure of 150-250 MPa and a holding time of 5-10 min.
[0019] Preferably, the nitric acid catalytic degreasing parameters are a temperature of 100-120° C., a nitric acid concentration of 3-5%, a flow rate of 3.5-4.8 ml / min, and a treatment time of 2-3 h.
[0020] Preferably, the thermal degreasing parameters are heating from room temperature to 280-350° C. at a heating rate of 1.5-2.5° C. / min and keeping the temperature for 1-1.5 h.
[0021] Preferably, the pre-sintering condition is to control the vacuum atmosphere to heat up to 1000-1100° C. at a heating rate of 2-4° C. / min, and keep the temperature for 60-90 minutes.
[0022] Preferably, the cooling treatment condition is to cool the sintered product to 560-650°C in vacuum in the furnace and then force cool it by passing argon until the temperature in the sintering furnace reaches 70-88°C.
[0023] The present application also provides a method for preparing a pick by laser cladding, comprising the following preparation steps:
[0024] (1) Surface treatment of pick: clean the surface of the pick, sandblast it, and preheat the pick;
[0025] (2) Laser cladding: The raw materials for the laser cladding layer are screened, mixed and ground, and then delivered to the surface of the pick by synchronous powder feeding method. They are irradiated with a high-energy laser beam and forced to cool to 10-20°C to form a laser cladding layer.
[0026] (3) The clad pick is nitrided, water-cooled to room temperature, tempered, and naturally cooled to obtain a laser clad high-performance pick.
[0027] Preferably, the blasting pressure in the step (1) is 0.75-1 MPa, the alumina particle size is 80-120 mesh, the blasting distance is 200-250 mm, the blasting angle is 45-60°, and the blasting time is 15-20 min.
[0028] Preferably, in step (1), the preheating temperature is 200-250° C. and the treatment time is 1-3 h.
[0029] Preferably, the process conditions of laser cladding in step (2) are as follows: the protective gas flow rate is 10-12 L / min, the powder feeding rate is 8-10 g / min, and the powder D 50 The particle size is 20-80μm, the powder feeder gas flow rate is 6-8L / min, the high-energy laser beam spot diameter is 1-3mm, the scanning speed is 800-1500mm / min, the power is 1.5-3kw, the overlap rate is 30-50%, and the cladding thickness is 2-3mm.
[0030] Preferably, in step (3), the nitriding treatment temperature is 450-550°C, and the nitriding treatment time is 4-6 hours; the tempering temperature is 150-350°C, and the holding time is 1-3 hours.
[0031] Preferably, in step (3), the nitriding treatment temperature is 500°C and the nitriding treatment time is 5h; the tempering temperature is 250°C and the holding time is 2h.
[0032] In summary, this application has the following beneficial effects:
[0033] The present application utilizes a mixture of multiple polymer materials to prepare a composite adhesive, which has good bonding properties and can be effectively removed during subsequent processing. Polyethylene is mixed with high density and low density, which not only ensures sufficient strength but also improves toughness, and is conducive to the uniformity of feeding and stability after molding; nitric acid catalytic degreasing and thermal degreasing treatment are combined to effectively remove the adhesive in the feed, while avoiding deformation and cracking of the pick body during the degreasing process, thereby ensuring the accuracy and dimensional stability of the pick; the sintering process strictly controls the heating rate and holding time to ensure sufficient densification and grain growth of the pick body at high temperature, thereby improving the hardness and wear resistance of the pick; after sintering, argon gas is used for forced cooling to reduce oxidation and deformation of the pick body at high temperature; the combination of salt bath and aging treatment further improves the hardness and toughness of the pick, helps to eliminate residual stress and tissue defects inside the pick, and improves the microstructure of the pick, making it have better fatigue resistance and wear resistance.
[0034] This application uses a variety of alloy powders as matrix materials, which have good toughness and processing performance. Hard phase materials such as tungsten carbide, boron carbide and aluminum oxide significantly improve the hardness and wear resistance of the coating. This composite material design can significantly improve the strength and toughness of the pick, making it have high hardness and wear resistance, and can meet the use requirements of the pick under harsh working conditions. Sandblasting and preheating the pick can reduce the thermal stress generated during the cladding process and improve the bonding strength of the cladding layer. By adjusting the parameters of the laser beam (such as spot diameter, scanning speed, power, etc.) and process parameters such as powder feeding amount and shielding gas flow, the thickness, composition and organizational structure of the cladding layer can be precisely controlled. It is efficient and energy-saving. Forced cooling can cause the cladding layer to cool down quickly to reduce thermal stress, which helps prevent the cladding layer from cracking or falling off, and reduce cracks and pores in the cladding layer. A series of post-treatments such as water cooling, nitriding, and tempering of the pick after laser cladding help to form a martensitic structure, which can further reduce thermal stress, improve hardness, toughness and wear resistance, and significantly improve the service life of the pick. DETAILED DESCRIPTION
[0035] The present application is further described in detail below with reference to the embodiments.
[0036] The iron-based alloy powder (article number: 058247); nickel-based alloy powder (article number: 110160); cobalt-based alloy powder (article number: 652998); tungsten carbide (article number: 0200718); boron carbide (article number: 03250) and aluminum oxide (article number: 06325917) described in the following examples or comparative examples are all purchased from Nangong Jingrui Alloy Products Co., Ltd.
[0037] Embodiments 1-3 provide a high-performance pick and a method for preparing the pick by laser cladding.
[0038] Example 1
[0039] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0040] The preparation process of the pick body specifically includes the following steps:
[0041] S1. Feed preparation:
[0042] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0043] S2, molding degreasing:
[0044] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0045] S3, sintering treatment:
[0046] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0047] S4, post-processing:
[0048] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0049] A method for preparing a pick by laser cladding comprises the following steps:
[0050] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0051] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0052] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0053] Example 2
[0054] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.20%, Si: 2.40%, Mn: 2.50%, Cr: 1.00%, Mo: 0.45%, Re: 0.03%, Nb: 0.03%, S: 0.02%, P: 0.005%, and the remainder is Fe and unavoidable impurities, and the cladding layer is composed of 13 parts of iron-based alloy powder, 9 parts of nickel-based alloy powder, 7 parts of cobalt-based alloy powder, 1.5 parts of tungsten carbide, 1.5 parts of boron carbide and 1.5 parts of aluminum oxide.
[0055] The preparation process of the pick body specifically includes the following steps:
[0056] S1. Feed preparation:
[0057] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 8 μm was added to a kneader together with a binder, kneaded at a temperature of 145°C for 105 min, and extruded into granules to obtain a tap density of 5.58 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 9 parts of polyethylene, 3.5 parts of polymethyl methacrylate, 1.5 parts of polypropylene, 1.5 parts of polytetrafluoroethylene and 1.5 parts of stearic acid, wherein the polyethylene is a mixture of 68% of high-density polyethylene and 32% of low-density polyethylene, and the amount of the binder added is 8% of the total mass of the alloy powder;
[0058] S2, molding degreasing:
[0059] The feed material is loaded into a mold and a pressure of 200 MPa is applied to the mold by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 110°C, nitric acid concentration 4%, flow rate 4.2 ml / min, and processing time 2.5 h; thermal degreasing parameters are heating from room temperature to 310°C at a heating rate of 2°C / min, and keeping the temperature for 1.25 h;
[0060] S3, sintering treatment:
[0061] The degreased blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to continue to be heated to 1050°C at a heating rate of 3°C / min, and pre-sintered for 75 minutes. After the insulation is completed, the temperature is continued to be increased to 1250°C at a heating rate of 2.5°C / min, and the insulation is carried out for 135 minutes, and then sintering is carried out. After the sintering is completed, the furnace is vacuum cooled to 600°C, and 12.5°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 80°C, and a dense blank is obtained.
[0062] S4, post-processing:
[0063] The dense blank in step S3 is heated to 1045°C and kept warm for 1.5 hours. The dense blank is immersed in a salt bath at 330°C, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 90 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 575°C at a heating rate of 1.5°C / min and kept warm for 6 hours for primary aging. Thereafter, the product is cooled to 500°C at a cooling rate of 6°C / min and kept warm for 3 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0064] A method for preparing a pick by laser cladding comprises the following steps:
[0065] (1) Surface treatment of pick: Clean the surface of the pick body and sandblast 100-mesh alumina at a spraying angle of 55° and a distance of 225 mm at a pressure of 0.85 MPa for 18 min. After the sandblasting, preheat the pick at 225°C for 2 h.
[0066] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The cladding surface material with a particle size of 50μm was delivered to the surface of the pick body. Under the conditions of shielding gas flow of 11L / min, powder feeding amount of 9g / min, and powder feeder gas flow of 7L / min, the spot diameter of the high-energy laser beam was controlled to be 2mm, the scanning speed was 1200mm / min, the power was 2.4kw, the overlap rate was 40%, and the preset powder material was irradiated. The cladding thickness was controlled to be 2.5mm, and the cladding layer was formed after forced cooling to 15℃ by high-pressure nitrogen spray.
[0067] (3) The clad pick is placed in nitrogen at 500°C for nitriding treatment for 5 hours, water cooled to room temperature, tempered, the water cooling temperature is controlled at 20°C, the tempering temperature is 250°C, the insulation time is 2 hours, and naturally cooled to obtain a laser clad high-performance pick.
[0068] Example 3
[0069] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.23%, Si: 2.60%, Mn: 2.60%, Cr: 1.20%, Mo: 0.50%, Re: 0.05%, Nb: 0.05%, S: 0.01%, P: 0.005%, and the remainder is Fe and unavoidable impurities, and the cladding layer is composed of 14 parts of iron-based alloy powder, 10 parts of nickel-based alloy powder, 8 parts of cobalt-based alloy powder, 2 parts of tungsten carbide, 2 parts of boron carbide and 2 parts of aluminum oxide.
[0070] The preparation process of the pick body specifically includes the following steps:
[0071] S1. Feed preparation:
[0072] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 8.5 μm was added to a kneader together with a binder, kneaded at 160°C for 120 min, and extruded into granules to obtain a tap density of 6.28 g / cm 3 The feed material is prepared for use, wherein the weight percentage of the binder is 80% polyethylene, 5% polymethyl methacrylate, 5% high-density polyethylene, 4% polypropylene, 3% polytetrafluoroethylene, and 3% stearic acid, and the amount of the binder added is 10% of the total weight of the alloy powder;
[0073] S2, molding degreasing:
[0074] The feed material is loaded into a mold and a pressure of 250 MPa is applied by a hydraulic press, and the pressure is maintained for 10 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 120°C, nitric acid concentration 5%, flow rate 4.8 ml / min, and processing time 3 hours; the thermal degreasing parameters are heating from room temperature to 350°C at a heating rate of 2.5°C / min, and keeping the temperature for 1.5 hours;
[0075] S3, sintering treatment:
[0076] The degreased blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to continue to be heated to 1100°C at a heating rate of 4°C / min, and pre-sintered for 90 minutes. After the insulation is completed, the temperature is continued to be increased to 1280°C at a heating rate of 3°C / min, and the insulation is carried out for 150 minutes, and sintering is carried out. After the sintering is completed, the furnace is vacuum cooled to 650°C, and 15°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 88°C, and a dense blank is obtained.
[0077] S4, post-processing:
[0078] The dense blank in step S3 is heated to 1060°C and kept at this temperature for 2 hours. The dense blank is immersed in a salt bath at 340°C, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping at this temperature for 120 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 600°C at a heating rate of 2°C / min and kept at this temperature for 8 hours for primary aging. Thereafter, the product is cooled to 550°C at a cooling rate of 8°C / min and kept at this temperature for 4 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0079] A method for preparing a pick by laser cladding comprises the following steps:
[0080] (1) Surface treatment of pick: Clean the surface of the pick body and sandblast 120-mesh alumina at a spraying angle of 60° and a distance of 250 mm at a pressure of 1 MPa. The sandblasting time is 20 min. After the sandblasting, preheat the pick at 250°C for 3 h.
[0081] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The raw material of the cladding layer with a particle size of 80μm is delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 12L / min, a powder feeding amount of 10g / min, and a powder feeder gas flow rate of 8L / min, the spot diameter of the high-energy laser beam is controlled to be 3mm, the scanning speed is 1500mm / min, the power is 3kw, and the overlap rate is 50%. The material is irradiated with a high-energy laser beam, the cladding thickness is controlled to be 3mm, and high-pressure nitrogen is sprayed to force cooling to 20℃ to form a cladding layer;
[0082] (3) The clad pick is placed in nitrogen at 550°C for nitriding treatment for 6 hours, water cooled to room temperature, tempered, the water cooling temperature is controlled at 30°C, the tempering temperature is 350°C, the insulation time is 3 hours, and naturally cooled to obtain a laser clad high-performance pick.
[0083] Comparative Example 1
[0084] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0085] The preparation process of the pick body specifically includes the following steps:
[0086] S1. Feed preparation:
[0087] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3The feed material is prepared for use, wherein the binder is a mixture of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is high-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0088] S2, molding degreasing:
[0089] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0090] S3, sintering treatment:
[0091] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0092] S4, post-processing:
[0093] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0094] A method for preparing a pick by laser cladding comprises the following steps:
[0095] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0096] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0097] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0098] Comparative Example 2
[0099] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0100] The preparation process of the pick body specifically includes the following steps:
[0101] S1. Feed preparation:
[0102] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is a mixture of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0103] S2, molding degreasing:
[0104] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0105] S3, sintering treatment:
[0106] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0107] S4, post-processing:
[0108] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0109] A method for preparing a pick by laser cladding comprises the following steps:
[0110] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0111] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0112] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0113] Comparative Example 3
[0114] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0115] The preparation process of the pick body specifically includes the following steps:
[0116] S1. Feed preparation:
[0117] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0118] S2, molding degreasing:
[0119] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and a degreased blank is obtained by thermal degreasing treatment. The thermal degreasing parameters are controlled to increase the temperature from room temperature to 280°C at a heating rate of 1.5°C / min and keep the temperature for 3 hours;
[0120] S3, sintering treatment:
[0121] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0122] S4, post-processing:
[0123] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0124] A method for preparing a pick by laser cladding comprises the following steps:
[0125] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0126] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0127] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0128] Comparative Example 4
[0129] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0130] The preparation process of the pick body specifically includes the following steps:
[0131] S1. Feed preparation:
[0132] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0133] S2, molding degreasing:
[0134] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is molded into a pick body, and nitric acid catalytic degreasing is performed to obtain a degreased blank. The nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 3 hours;
[0135] S3, sintering treatment:
[0136] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0137] S4, post-processing:
[0138] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0139] A method for preparing a pick by laser cladding comprises the following steps:
[0140] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0141] (2) Laser cladding: D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0142] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0143] Comparative Example 5
[0144] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0145] The preparation process of the pick body specifically includes the following steps:
[0146] S1. Feed preparation:
[0147] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0148] S2, molding degreasing:
[0149] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0150] S3, sintering treatment:
[0151] The degreased blank in step S2 is placed in a vacuum batch furnace, heated to 1220°C at a heating rate of 2.2°C / min, kept warm for 120 minutes, and sintered. After sintering, the blank is vacuum cooled to 560°C in the furnace, and forcedly cooled by 10°C argon gas until the temperature in the sintering furnace reaches 70°C, thereby obtaining a dense blank.
[0152] S4, post-processing:
[0153] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0154] A method for preparing a pick by laser cladding comprises the following steps:
[0155] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0156] (2) Laser cladding: D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0157] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0158] Comparative Example 6
[0159] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0160] The preparation process of the pick body specifically includes the following steps:
[0161] S1. Feed preparation:
[0162] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0163] S2, molding degreasing:
[0164] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0165] S3, sintering treatment:
[0166] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0167] S4, post-processing:
[0168] The dense blank in step S3 is heated to 1030°C, kept warm for 1 hour, air-cooled to room temperature, heated to 550°C at a heating rate of 1°C / min, kept warm for 4 hours for primary aging, then cooled to 450°C at a cooling rate of 4°C / min, kept warm for 2 hours for secondary aging, and cooled to room temperature with the furnace after the insulation is completed to obtain the required high-performance pick body.
[0169] A method for preparing a pick by laser cladding comprises the following steps:
[0170] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0171] (2) Laser cladding: After screening, mixing and grinding the raw materials for the laser cladding layer, the raw materials with a D50 particle size of 20 μm are delivered to the surface of the pick body by the synchronous powder feeding method. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam is controlled to be 1 mm, the scanning speed is 800 mm / min, the power is 1.5 kW, and the overlap rate is 30%. The cladding thickness is controlled to be 2 mm, and the laser cladding layer is formed after forced cooling to 10 °C by high-pressure nitrogen spray;
[0172] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0173] Comparative Example 7
[0174] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0175] The preparation process of the pick body specifically includes the following steps:
[0176] S1. Feed preparation:
[0177] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0178] S2, molding degreasing:
[0179] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0180] S3, sintering treatment:
[0181] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0182] S4, post-processing:
[0183] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0184] A method for preparing a pick by laser cladding comprises the following steps:
[0185] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a pressure of 0.75 MPa for 15 minutes;
[0186] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0187] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, tempered, and the water cooling temperature is controlled at 20°C. The tempering temperature is 150°C, the insulation time is 1 hour, and the laser cladding high-performance pick is obtained after natural cooling.
[0188] Comparative Example 8
[0189] A high-performance pick comprises a pick body and a cladding layer clad on the surface of the pick body, wherein the pick body is composed of the following raw materials in weight percentage: C: 0.15%, Si: 2.10%, Mn: 2.40%, Cr: 0.80%, Mo: 0.35%, Re: 0.01%, Nb: 0.01%, S: 0.01%, P: 0.005%, and the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12 parts of iron-based alloy powder, 8 parts of nickel-based alloy powder, 6 parts of cobalt-based alloy powder, 1 part of tungsten carbide, 1 part of boron carbide and 1 part of aluminum oxide.
[0190] The preparation process of the pick body specifically includes the following steps:
[0191] S1. Feed preparation:
[0192] The raw materials of the pick body are mixed and prepared by gas atomization method. 50 The alloy powder with a particle size of 7.5 μm was added to a kneader together with a binder, kneaded at a temperature of 130°C for 90 min, and extruded into granules to obtain a tap density of 5.38 g / cm 3 The feed material is prepared for use, wherein the binder is composed of 8 parts of polyethylene, 3 parts of polymethyl methacrylate, 1 part of polypropylene, 1 part of polytetrafluoroethylene and 1 part of stearic acid, wherein the polyethylene is a mixture of 65% of high-density polyethylene and 35% of low-density polyethylene, and the amount of the binder added is 6% of the total mass of the alloy powder;
[0193] S2, molding degreasing:
[0194] The feed material is loaded into a mold and a pressure of 150 MPa is applied by a hydraulic press, and the pressure is maintained for 5 minutes, and the pick body is formed by compression molding, and nitric acid catalytic degreasing and thermal degreasing are performed to obtain a degreased blank, and the nitric acid catalytic degreasing parameters are controlled as follows: temperature 100°C, nitric acid concentration 3%, flow rate 3.5 ml / min, and processing time 2h; thermal degreasing parameters are heating from room temperature to 280°C at a heating rate of 1.5°C / min, and keeping the temperature for 1h;
[0195] S3, sintering treatment:
[0196] The debinded blank in step S2 is placed in a vacuum batch furnace, and the vacuum atmosphere is controlled to heat up to 1000°C at a heating rate of 2°C / min, and pre-sintered at a temperature of 60 minutes. After the insulation is completed, the temperature is further increased to 1220°C at a heating rate of 2.2°C / min, and the temperature is kept for 120 minutes for sintering. After the sintering is completed, the furnace is vacuum cooled to 560°C, and 10°C argon is passed for forced cooling until the temperature in the sintering furnace reaches 70°C, so as to obtain a dense blank.
[0197] S4, post-processing:
[0198] The dense blank in step S3 is heated to 1030°C and kept warm for 1 hour. The dense blank is immersed in a 320°C salt bath, wherein the salt solution contains equal amounts of potassium nitrate and sodium nitrate. After keeping warm for 60 seconds, the blank is air-cooled to room temperature. The product after the salt bath treatment is heated to 550°C at a heating rate of 1°C / min and kept warm for 4 hours for primary aging. Thereafter, the product is cooled to 450°C at a cooling rate of 4°C / min and kept warm for 2 hours for secondary aging. After the insulation is completed, the product is cooled to room temperature with the furnace to obtain the desired high-performance pick body.
[0199] A method for preparing a pick by laser cladding comprises the following steps:
[0200] (1) Surface treatment of pick: Clean the surface of the pick and blast it with 80-mesh aluminum oxide at a spraying angle of 45° and a distance of 200 mm at a spraying pressure of 0.75 MPa. The blasting time is 15 min. After the blasting, preheat the pick at 200°C for 1 h.
[0201] (2) Laser cladding: After the raw materials of the laser cladding layer are screened, mixed and ground, the D 50 The raw material of the cladding layer with a particle size of 20 μm was delivered to the surface of the pick body. Under the conditions of a protective gas flow rate of 10 L / min, a powder feeding amount of 8 g / min, and a powder feeder gas flow rate of 6 L / min, the spot diameter of the high-energy laser beam was controlled to be 1 mm, the scanning speed was 800 mm / min, the power was 1.5 kW, and the overlap rate was 30%. The cladding thickness was controlled to be 2 mm, and the laser cladding layer was formed after forced cooling to 10 ° C by high-pressure nitrogen spray.
[0202] (3) The clad pick is placed at 450°C for nitriding treatment for 4 hours, water-cooled to room temperature, and the water cooling temperature is controlled at 20°C. After natural cooling, a laser clad high-performance pick is obtained.
[0203] Performance Testing
[0204] The comprehensive performance of the laser cladding high-performance picks prepared in Examples 1-3 and Comparative Examples 1-8 of the present application is as follows:
[0205] Bonding strength: tested in accordance with national standard GB / T8642-2002;
[0206] Bending strength: tested in accordance with national standard GB / T 6569-86;
[0207] Hardness: Tested using HR-150AI Rockwell hardness tester;
[0208] Wear rate: The test was conducted using an MLS-225 wet sand rubber wheel wear tester, with the following test parameters: rubber wheel speed: 240r / min; rubber wheel diameter: 178mm; rubber wheel hardness: 60 (Shore hardness); mortar ratio: 1000g water: 1500g sand; load: 10Kgf; wear time: 50m; rubber wheel revolutions: about 12,000 revolutions; abrasive: 40-70 mesh quartz sand; pre-grind for 12,000 revolutions, then formally grind for 12,000 revolutions, calculate the weight difference before and after wear, which is the weight loss, and divide the weight loss by the number of revolutions of the rubber wheel to get the wear rate.
[0209] Table 1 Performance parameters of laser cladding high performance pick
[0210] Test performance Bonding strength (MPa) Flexural strength (MPa) Pick hardness (HRA) <![CDATA[Wear rate (mm 3 / N·m)]]> Example 1 422.4 3326 93.2 <![CDATA[2.2×10 -5 ]]> Example 2 431.8 3451 94.5 <![CDATA[1.8×10 -5 ]]> Example 3 435.7 3465 95.7 <![CDATA[1.7×10 -5 ]]> Comparative Example 1 384.2 2976 82.5 <![CDATA[12.1×10 -5 ]]> Comparative Example 2 356.2 2897 83.4 <![CDATA[11.5×10 -5 ]]> Comparative Example 3 345.7 2913 82.9 <![CDATA[12.3×10 -5 ]]> Comparative Example 4 365.4 2967 82.1 <![CDATA[12.5×10 -5 ]]> Comparative Example 5 386.4 2983 79.6 <![CDATA[15.4×10 -5 ]]> Comparative Example 6 397.4 2971 80.3 <![CDATA[14.7×10 -5 ]]> Comparative Example 7 381.5 2843 82.5 <![CDATA[12.5×10 -5 ]]> Comparative Example 8 384.9 2969 83.7 <![CDATA[11.4×10 -5 ]]>
[0211] The present application discloses a method for preparing high-performance picks by laser cladding. It can be seen from the examples that the picks prepared by the present application have small porosity and internal stress, enhanced hardness, wear resistance and impact resistance, high bonding strength between the laser cladding layer and the pick, and no obvious defects such as cracks and pores exist. The prepared laser cladding layer has high hardness and wear resistance, and the coating has excellent mechanical properties, and the prepared high-performance picks have excellent comprehensive performance.
[0212] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-performance pick, comprising a pick body and a cladding layer clad on the surface of the pick body, characterized in that: The pick body is composed of the following raw materials in weight percentage: C: 0.15-0.23%, Si: 2.10-2.60%, Mn: 2.40-2.60%, Cr: 0.80-1.20%, Mo: 0.35-0.50%, Re: 0.01-0.05%, Nb: 0.01-0.05%, S<0.02%, P<0.01%, the balance is Fe and unavoidable impurities, and the cladding layer is composed of 12-14 parts of iron-based alloy powder, 8-10 parts of nickel-based alloy powder, 6-8 parts of cobalt-based alloy powder, 1-2 parts of tungsten carbide, 1-2 parts of boron carbide and 1-2 parts of aluminum oxide; The preparation process of the pick body specifically comprises the following steps: S1. Feed preparation: The raw materials of the pick body are mixed to prepare alloy powder according to weight percentage, the alloy powder and the binder are added into a kneader, kneaded at a temperature of 130-160° C. for 90-120 minutes, and extruded and granulated to obtain feed material for standby use; S2, molding degreasing: The feed material is molded into a pick body, and then subjected to nitric acid catalytic degreasing and thermal degreasing processes to obtain a degreased blank; S3, sintering treatment: The degreased blank in step S2 is placed in a vacuum batch furnace, and after pre-sintering, the temperature is further increased to 1220-1280°C at a heating rate of 2.2-3°C / min, and the temperature is kept for 120-150min, and then sintered. After sintering, a dense blank is obtained by cooling. S4, post-processing: The dense blank in step S3 is heated to 1030-1060°C and kept warm for 1-2h. The dense blank is immersed in a salt bath at 320-340°C, kept warm for 1-2min, and then air-cooled to room temperature. The product after the salt bath treatment is heated to 550-600°C at a heating rate of 1-2°C / min, kept warm for 4-8h for primary aging, and then cooled to 450-500°C at a cooling rate of 4-8°C / min, and kept warm for 2-4h for secondary aging. After the insulation is completed, it is cooled to room temperature with the furnace to obtain the required high-performance pick body.
2. The high performance pick according to claim 1, characterized in that: The adhesive in step S1 is composed of 8-10 parts of polyethylene, 3-4 parts of polymethyl methacrylate, 1-2 parts of polypropylene, 1-2 parts of polytetrafluoroethylene and 1-2 parts of stearic acid, wherein the polyethylene is a mixture of 65-70% of high-density polyethylene and 30-35% of low-density polyethylene.
3. The high performance pick according to claim 1, characterized in that: The molding conditions of step S2 are molding pressure of 150-250MPa, holding time of 5-10min, nitric acid catalytic degreasing parameters of temperature of 100-120°C, nitric acid concentration of 3-5%, flow rate of 3.5-4.8ml / min, and processing time of 2-3h; the thermal degreasing parameters are heating from room temperature to 280-350°C at a heating rate of 1.5-2.5°C / min, and keeping warm for 1-1.5h.
4. The high performance pick according to claim 1, characterized in that: The pre-sintering conditions in step S3 are to control the vacuum atmosphere and continue to heat up to 1000-1100° C. at a heating rate of 2-4° C. / min, and keep the temperature for 60-90 minutes.
5. The high performance pick according to claim 1, characterized in that: The cooling treatment condition of step S3 is to cool the furnace to 560-650° C. in vacuum and then pass argon gas for forced cooling until the temperature in the sintering furnace reaches 70-88° C.
6. A method for preparing the high-performance pick according to any one of claims 1 to 5 by laser cladding, characterized in that: The method comprises the following preparation steps: (1) Surface treatment of pick: clean the surface of the pick, sandblast it, and preheat it; (2) Laser cladding: The raw materials for the laser cladding layer are screened, mixed and ground, and then delivered to the surface of the pick body by synchronous powder feeding method. A high-energy laser beam is used for irradiation, and the laser cladding layer is formed after forced cooling to 10-20°C. (3) The clad pick is nitrided, water-cooled to room temperature, tempered, and naturally cooled to obtain a laser clad high-performance pick.
7. The method for preparing a pick by laser cladding according to claim 6, characterized in that: The preheating conditions in step (1) are a temperature of 200-250° C. and a treatment time of 1-1.5 h.
8. The method for preparing a pick by laser cladding according to claim 6, characterized in that: The process conditions of laser cladding in step (2) are as follows: the protective gas flow rate is 10-12 L / min, the powder feeding rate is 8-10 g / min, and the powder D 50 The particle size is 20-80μm, the powder feeder gas flow rate is 6-8L / min, the high-energy laser beam spot diameter is 1-3mm, the scanning speed is 800-1500mm / min, the power is 1.5-3kw, the overlap rate is 30-50%, and the cladding thickness is 2-3mm.
9. The method for preparing a pick by laser cladding according to claim 6, characterized in that: In the step (3), the nitriding treatment temperature is 450-550° C., and the nitriding treatment time is 4-6 hours; the tempering temperature is 150-350° C., and the insulation time is 1-3 hours.
Citation Information
Patent Citations
Strengthen process for pick head by laser fusing and coating wear-resistant coating
CN101338428A
High performance cutting pick and manufacturing method thereof
CN108977631A